Deteksi Virus Rabies pada Kasus Ante-Mortem dengan RT-PCR - -, Agustiningsih; Puspa, Kartika Dewi; Nugraha, Arie Ardiansyah; Setiawaty, Vivi (Central Basic Biomedical and Health Technology, 2014)
Rabies virus detection using Reverse Transcriptase Polymerase Chain Reaction (RT â PCR) was considered to have high sensitivity and specificity. This method is relatively faster and easy to perform in comparison with other methods such as Fluorescent Antibody Test (FAT) and Mouse Inoculation Test (MIT). Therefore, the RT PCR method is used as ante mortem diagnosis of rabies. A total of 74 specimens such as saliva, conjuctival swabs and under tongue swabs were collected from the bites of animal transmitting rabies cases. The 74 specimens were collected from 28 human cases of suspected rabies outbreaks in 2009-2013 that has been tested in the Virology Laboratory, Center for Biomedical and Basic Technology of Health. All specimens examined by RT - PCR method using two primer pairs that amplify the partial gene regions of the N and G genes of the rabies virus. Two of the 74 specimens gave positive results of rabies by RT - PCR, i.e saliva and under-tongue swab from human cases of animal bites in 2009. RT-PCR assay can be used for ante mortem diagnosis of the rabies virus. The laboratory results are influenced by the type of specimen and collection time.Key words : Rabies, Outbreak, RT-PCRÂ AbstrakDeteksi virus rabies menggunakan metode Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) dinilai memiliki sensitivitas dan spesifisitas yang tinggi. Kemudahan pengerjaan dan hasil pemeriksaan yang relatif cepat dibandingkan dengan metode Fluorescent Antibody Test (FAT) dan Mouse Inoculation Test (MIT) yang merupakan metode standar WHO yang menjadikan RT-PCR lebih banyak digunakan untuk deteksi ante mortem virus rabies. Sebanyak 74 spesimen kasus gigitan hewan penular rabies (GHPR) yaitu saliva, apus selaput mata dan apus bawah lidah yang berasal dari 28 kasus tersangka rabies pada kejadian luar biasa pada tahun 2009-2013 yang telah diperiksa oleh laboratorium Virologi Pusat Biomedis dan Teknologi Dasar Kesehatan. Seluruh spesimen diperiksa dengan metode RT-PCR menggunakan 2 pasang primer yaitu primer yang mengamplifikasi sebagian region pada gen N dan gen G dari virus rabies tersebut. Dua dari 74 spesimen memberikan hasil positif rabies berdasarkan hasil pemeriksaan dengan RT-PCR, yaitu spesimen saliva dan swab bawah lidah dari kasus gigitan anjing pada tahun 2009. Pemeriksaan ante mortem terhadap virus rabies dapat menggunakan metode RT-PCR dengan memperhatikan waktu pengambilan dan jenis spesimen.Kata Kunci : Rabies, KLB, RT-PCR